A Study On The Concepts And Themes Of Color And Light In The Exquisite Islamic Architecture - Mahdinejad, J.; Zarghami, E.; Sadeghi Habibabad, A. (University of Eloued جامعة الوادي, 2016)
It should be considered that how the existence of light and color in the patterns has been effective in the environmental psychology and how the space is defined in terms of these two elements? And whether the sole use of light and color in the historical architecture was to represent meaning? The present study adopts a descriptive-analytical approach to review and explain the semantic elements of light and color, their application and conceptual features in the historical architecture and hence examines these two distinct elements in the art and architecture of the past and tries to find their semantic features to the extent that have influenced the face and essence of modern architecture in the hope of providing useful insights for the modern architecture.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: Islamic architecture, light, color, concepts, exquisite architecture